Accounting Students Perception of Information Technology Knowledge That Must Be Mastered by An Accountant (Case Study of Accounting Students in the Faculty of Economics and Business Tanjungpura University) - DAMAYANTI, CINTHIA ANDINI (Jurnal KIAFE, 2020)
This study aims to determine the perceptions of accounting students at the Faculty of Economics and Business, University of Tanjungpura on information technology knowledge that must be mastered by accountants. This type of research is a case study on students of the Accounting Study Program, Faculty of Economics and Business, Tanjungpura University. The data collection method used is an online questionnaire or what is called Google Form. The data analysis techniques used to answer the problem formulation include: 1) using the Data Normality Test and Hypothesis Test which is equipped with steps to make decisions, the analysis tool uses the Independent Sample T-test, 2) using the Data Normality Test and Hypothesis Testing which is equipped with steps for making decisions, analysis tools using One Way Anova (One Way - Anova).Keywords:Accountant, Google Form, Normality Test, Independent Simple T-Test, One-Way Anova.